71.1k views
0 votes
Assemble the proof by dragging tiles to the statements and reasons columns.

PLEASE HELP

Assemble the proof by dragging tiles to the statements and reasons columns. PLEASE-example-1
User Dillan
by
6.6k points

2 Answers

2 votes

Answer:

Explanation:

m<ABD = 52 Given

BC bisects <ABD Given

m<ABC = m<CBD Definition of angle bisector.

m<ABC +m<CBD = m<ABD Angle addition postulate.

m<ABC +m<CBD = 52 Substitution

m<ABC + m<ABC= 52 Substitution

2m<ABC = 52 Combining like angles

2(m<ABC) = 52 Addition

m<ABC=26 Division Property

User Elroy
by
5.7k points
0 votes

m<ABD = 52 Given

BC bisects <ABD Given

m<ABC = m<CBD Definition of angle bisector.

m<ABC +m<CBD = m<ABD Angle addition postulate.

m<ABC +m<CBD = 52 Substitution

m<ABC + m<ABC= 52 Substitution

2m<ABC = 52 Combining like angles

m<ABC = 26 Division property of equality.

User Niko Fohr
by
5.0k points